Diiodine–Triethylsilane System: Reduction of N-Sulfonyl Aldimines to N-Alkylsulfonamides - Jiang, Jin; Xiao, Lili; Li, Yu-Long (Synlett, 2020)
Because molecular iodine and hydrosilanes are stable to both air and moisture, reactions using these reagents are easy to operate and require mild reaction conditions. Molecular iodine and a hydrosilane were used to reduce N-sulfonyl aldimines to the corresponding N-alkylsulfonamides. This transformation is a practical method for the synthesis of N-alkylsulfonamides.
Keywords: imines; iodine; reduction; hydrosilanes; sulfonamides